Accounting conservatism and fair value model selection of investment property in ASEAN - Kholilah, Kholilah; Rahman, Aulia Fuad; Ghofar, Abdul; Atmini, Sari; Palil, Mohd Rizal (Journal of Social Economics Research, 2026)
This research aimed to investigate the effect of debt levels and the moderating role of a country’s institutional factors influencing the choice of fair value models in ASEAN property and real estate companies. The examination of a country’s institutional factors as a moderating variable was important since debt policy reflects corporate strategy and national governance. Logistic and moderation regression analyses on 328 companies from 2018 to 2023 showed that higher levels of corporate debt reduced the probability of adopting the fair value model, as inflated asset valuations were avoided. The moderating influence of the country’s institutional factors increased the negative effect. Furthermore, this research added empirical evidence about using positive accounting and new institutional theory to explain the selection of policies in cross-country research because the complexity of developing and implementing standards was different. The results showed that developing countries did not use the fair value model, following the inability to maintain banking trust as the primary source of funding. The Ministry of Finance and similar authorities in the five ASEAN countries should coordinate with professional associations to prepare accounting systems and relevant regulatory documents, as well as support reducing the gap between IFRS and local standards to create favorable conditions for companies in applying IFRS in the future.